1985
DOI: 10.1080/03067318508077022
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 23 Polycyclic Aromatic Hydrocarbons in Atmospheric Particulate Matter of the Paris Area and Photolysis by Sunlight

Abstract: Twenty-three polycyclic aromatic hydrocarbons (PAH) were determined in atmospheric particulate matter in 4 places of the Paris area at several times of the year. Fractionation was performed by reversed-phase high-pressure liquid chromatography. Determination was done by recording emission or excitation fluorescence spectra via a stopped-flow technique. Triphenylene was also extemporaneously determined by its phosphorescence spectrum at low temperature. Among the PAH determined dibenz(e,ghi)perylene has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Interestingly, maximum values of all the 16 congeners (except for naphthalene) were recorded in S. acuminata inhabiting close to pollution sources (e.g., Baumard et al 1999).The abundance of HMW PAHs in S. acuminata was also typically encountered in atmospheric particles and urban aerosols (Muel and Saguem 1985;Sicre et al 1987), due to their low water solubility, low microbial degradation rate (Readman et al 1982), and high particulate affinity, compared with LMW PAHs. However, it should be noted that naphthalene was the most abundant LMW PAH, followed by phenanthrene.…”
Section: Variations Of Pah Congener Residues In Bivalve Tissuesmentioning
confidence: 96%
“…Interestingly, maximum values of all the 16 congeners (except for naphthalene) were recorded in S. acuminata inhabiting close to pollution sources (e.g., Baumard et al 1999).The abundance of HMW PAHs in S. acuminata was also typically encountered in atmospheric particles and urban aerosols (Muel and Saguem 1985;Sicre et al 1987), due to their low water solubility, low microbial degradation rate (Readman et al 1982), and high particulate affinity, compared with LMW PAHs. However, it should be noted that naphthalene was the most abundant LMW PAH, followed by phenanthrene.…”
Section: Variations Of Pah Congener Residues In Bivalve Tissuesmentioning
confidence: 96%
“…The theory of this origin index was based on the fact that the petrogenic contamination was characterized by the predominance of the lower molecular weight PAHs (tri-and tetra-aromatics) (Neff 1979;Wise et al 1988;Berner et al 1990), while the higher molecular weight PAHs dominate in pyrolytic PAH contamination (Muel and Saguem 1985). Examination of Table 3, shows that the LMW/HMW are higher than 1 (between 9 and 77) indicating the influence of petrogenic contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that parent PAHs were primarily produced by uncompleted combustion of fossil fuels and plant materials or natural diagenesis (Laflamme et al, 1978;Lake et al, 1979;Yunker et al, 1996). Of the combustion-derived PAHs, LMW PAHs (178-202) are primarily produced at low to moderate temperatures (Lake et al, 1979;Yunker et al, 1996), while HMW PAHs (228-276) are generated at high temperatures (Muel et al, 1985). It should be noted that petroleum-derived residues also contain relatively high abundances of 2-ring and 3-ring PAHs (Tolosa et al, 1996;Mai et al, 2003).…”
Section: Evaluation Of Petrogenic Versus Pyrogenic Sourcesmentioning
confidence: 97%